2013
DOI: 10.1186/1471-2334-13-206
|View full text |Cite
|
Sign up to set email alerts
|

Low serum total nitrite and nitrate levels in severe leptospirosis

Abstract: BackgroundThe relationship between inducible nitric oxide synthatase activity and disease severity in leptospirosis is unclear. Nitric oxide is converted to nitrites and nitrates, thus nitrite and nitrate levels (NOx) in serum are considered surrogate markers for nitric oxide. NOx are excreted through the kidneys, and elimination is diminished in renal impairment. We assessed the correlation of NOx with disease severity in patients with leptospirosis, compared with healthy controls and non-leptospirosis fever … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…23 There has been much debate as to whether uncorrected levels of nitrate/nitrite (NOx) are a reliable index of NO activity. In malaria, high NOx levels have been shown to be associated with worse prognosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…23 There has been much debate as to whether uncorrected levels of nitrate/nitrite (NOx) are a reliable index of NO activity. In malaria, high NOx levels have been shown to be associated with worse prognosis.…”
mentioning
confidence: 99%
“…There has been much research into this subject over the past decade, and several potential biomarkers have already been earmarked for further investigation. 22 These include biochemical molecules such as nitric oxide and its metabolites, 23 cytokines such as IL-1, 6, TNF-, 24 polymorphisms of human leukocyte antigen (HLA) and cytokine genes, 25 human serum mannose binding lectin (which identifies pathogens activating the immune system), soluble ST2 receptors, long pentraxin PTX3 and copeptin. 26 …”
mentioning
confidence: 99%
“…In severe leptospirosis, since there is renal impairment, it is possible that the raised NO level may not reflect increased synthetic activity but reduced clearance of NO via the kidneys. In fact a recently published paper by Kalugalage et al [ 40 ] demonstrated that, as in malaria, the corrected NO concentration (corrected for renal impairment) in patients with severe leptospirosis is actually lower than in non-leptospirosis fever patients and patients with mild leptospirosis. The pathophysiological basis for this phenomenon remains elusive.…”
Section: Methodsmentioning
confidence: 99%
“…In severe leptospirosis, since there is often renal impairment, it is possible that the raised NO levels reflect reduced renal clearance of NO rather than increased synthesis. Kalugalage et al demonstrated that, similar to what was seen in malaria, the corrected total NOx (nitrite+nitrate) concentration (i.e., corrected for renal impairment) in patients with severe leptospirosis was actually lower than in patients with mild leptospirosis and non-leptospirosis fever [16]. The pathophysiological basis for this pheno-menon remains elusive.…”
Section: Ceylon Medical Journalmentioning
confidence: 96%